A Novel Methodological Approach to assessing Deformation and Force in Barrette Walls using FEM and ANOVA - Vo, Luan Nhat; Dang, Truong Xuan; Nguyen, Phuong Tuan; Tran, Hoa Van Vu; Nguyen, Tuan Anh (Engineering, Technology & Applied Science Research, 2024)
This research advances the understanding of deep excavation impacts by integrating a refined Finite Element Method (FEM) analysis with empirical data, specifically examining the behavior of retaining structures in urban environments. Unlike prior studies that predominantly relied on theoretical models, this paper combines FEM with statistical methods, particularly ANOVA, to identify critical factors affecting the performance of barrette walls during excavation. The primary objective of this study is to analyze the deformation and force behaviors at various depths, thereby enhancing the predictive capabilities of existing models. The findings highlight significant variations in horizontal displacements (Uy) and vertical displacements (Uz) across different excavation stages, with notable mean differences ranging from 0.000529420 m to 0.000700240 m for Uy and -0.017563652 m for Uz. Axial forces (N1) also show significant increases with depth, reaching a mean difference of 516.137991 kN/m. These results underscore the importance of adaptive design strategies in deep excavation projects. However, the study is limited by the specific geological conditions and the scope of empirical data used for model validation. Practical recommendations include enhancing real-time monitoring systems and applying refined methodologies.